Carl Schmitt against mass democracy: reinterpreting the crisis of parliamentary democracy - Taşçıoğlu, İrem (İstanbul Bilgi Üniversitesi Yayınları, 2021)
ABSTRACT: Carl Schmitt’s work on The Crisis of Parliamentary Democracy has been subject to a new scholarly interest within the context of the debates on populism. Most accounts emphasized the anti-liberal elements in his thought that are discernible in those parts of the book that elaborate on the opposition between liberalism and democracy. This paper argues that such emphasis tends to oversee the analysis developed by Schmitt with regard to the decline of the nineteenth century parliamentarism in the same book. Suggesting that Schmitt nostalgically idealizes nineteenth century parliamentarism as an instance of bourgeois domination and blames mass democracy for its deterioration, this paper puts forth a different portrayal of Schmitt who is an anti-democrat and committed to preserving bourgeois social/political order. This paper finalizes by suggesting that a rigorous analysis of Schmitt’s anti-democratic politics would offer us a new lens to interrogate the polemical side of his anti-liberalism. This would in turn disclose the shortcomings of portraying Schmitt as a principled anti-liberal.

ÖZET: Carl Schmitt’in Parlamenter Demokrasinin Krizi isimli çalışması popülizm tartışmaları bağlamında yeni bir akademik ilginin konusu oldu. Bu tartışmaların parçası olan çoğu yaklaşım, Schmitt’in düşüncesinin, bu kitabın liberalizm ve demokrasinin karşıtlığı üzerine düşündüğü kısımlarında teşhis edilebilen anti-liberal öğeleri üzerine vurgu yaptı. Bu yazı, böylesi bir vurgunun Schmitt’in ondokuzuncu yüzyıl parlamentoculuğunun düşüşü üzerine aynı kitapta geliştirdiği analizi görmezden geldiğini iddia etmektedir. Ayrıca, Schmitt’in burjuva hakimiyetinin bir kertesi olarak ondokuzuncu yüzyıl parlamentoculuğunu nostaljik bir biçimde idealize ettiğini ve onun yozlaşmasının sorumlusu olarak kitle demokrasisini gördüğünü öne sürerek, burjuva sosyal/politik düzenine bağlı bir anti-demokrat Schmitt portresi ortaya koyar. Bu yazı Schmitt’in anti-demokratik siyasetinin titiz bir incelemesinin onun anti-liberalizmin polemiksel yönünü soruşturmak için aslında yeni bir mercek sunduğunu iddia ederek sonlanır. Bu yazının iddiasına göre, böylesi bir mercek Schmitt’i ilkeli bir anti-liberal olarak resmetmenin eksik yanlarını da açığa çıkaracaktır.
Carl Schmitt kitle demokrasisine karşı: parlamenter demokrasinin krizi’ni yeniden yorumlamak
Keywords: Carl Schmitt; The Crisis of Parliamentary Democracy; liberalism; elitism; mass democracy; parliament; Parlamenter Demokrasinin Krizi; liberalizm; elitizm; kitle demokrasisi; parlamento